High‐resolution three‐dimensional chromatin profiling of the Chinese hamster ovary cell genome. Issue 2 (20th November 2020) - Bevan, Stephen; Schoenfelder, Stefan; Young, Robert J.; Zhang, Lin; Andrews, Simon; Fraser, Peter; O'Callaghan, Peter M.
Abstract: Chinese hamster ovary (CHO) cell lines are the pillars of a multibillion‐dollar biopharmaceutical industry producing recombinant therapeutic proteins. The effects of local chromatin organization and epigenetic repression within these cell lines result in unpredictable and unstable transgene expression following random integration. Limited knowledge of the CHO genome and its higher order chromatin organization has thus far impeded functional genomics approaches required to tackle these issues. Here, we present an integrative three‐dimensional (3D) map of genome organization within the CHOK1SV® 10E9 cell line in conjunction with an improved, less fragmented CHOK1SV 10E9 genome assembly. Using our high‐resolution chromatin conformation datasets, we have assigned ≈90% of sequence to a chromosome‐scale genome assembly. Our genome‐wide 3D map identifies higher order chromatin structures such as topologically associated domains, incorporates our chromatin accessibility data to enhance the identification of active cis ‐regulatory elements, and importantly links these cis ‐regulatory elements to target promoters in a 3D promoter interactome. We demonstrate the power of our improved functional annotation by evaluating the 3D landscape of a transgene integration site and two phenotypically different cell lines. Our work opens up further novel genome engineering targets, has the potential to inform vital improvements for industrial biotherapeutic production, and represents a significant advancement for CHO cell line development. Abstract : In this work Bevan and colleagues generate a comprehensive 3D genome map of a site‐specific integration (SSI) CHO host cell line using a combination of ATAC‐Seq, Hi‐C, and Promoter‐Capture Hi‐C. These datasets are used to identify higher order chromatin structures such as topologically‐associated domains (TADs), and puts them in the context of a genome‐wide 3D promoter interactome. The combination of such datasets may be used to design cell engineering approaches for improving CHO performance in the bioprocessing environment.